An Unusual Valence State: Trivalent Europium in Intermetallic Eu2Ir3Al9. Issue 14 (8th February 2019) - Stegemann, Frank; Block, Theresa; Klenner, Steffen; Janka, Oliver
Abstract: Eu2 Ir3 Al9, synthesized from the elements in tantalum tubes, is one of the rare examples for trivalent europium in the field of intermetallic compounds. The compound crystallizes in the Y2 Co3 Ga9 ‐type structure (space group Cmcm ), with lattice parameters fitting in between the isostructural samarium and gadolinium compounds. In the crystal structure, the Eu atoms form Al3 ‐triangle‐centered honeycomb layers and exhibit a coordination number of 17 in the shape of a fivefold‐capped hexagonal prism (Eu@Ir6 Al6 +Al5 ). Magnetic measurements indicate an overall low susceptibility, in line with van Vleck paramagnetism caused by the Eu 3+ cations. Fits of the susceptibility yield a coupling constant of λ =290(10) K and an effective magnetic moment of μ eff =4.56(1) μB, in line with a slight hybridization of the 7 F 0 and 7 F 1 state. 151 Eu Mössbauer spectroscopic investigations unambiguously prove the presence of solely Eu 3+ in the bulk material. Abstract : Eu2 Ir3 Al9, a rare example of an intermetallic compound that exhibits solely trivalent Eu atoms, is reported. The valence state was investigated by magnetic and 151 Eu Mössbauer spectroscopic measurements.